Diseño y construcción de una máquina roladora de tubo - Molina Andrade, Kevin David (2023)
The present project is defined according to different parameters focused on the inversion of rotation of a single-phase motor with the purpose of applying it to a rolling process, the construction of a structure itself that serves as the basis for the operation in a horizontal and vertical facilitating the work of the operator.